Africa development indicators. the potential, the problem, the promise. (Africa development indicators ;, 2009)
Africa Development Indicators 2008/09 (ADI) provides the most detailed collection of data on Africa available in one volume. It puts together data from different sources, making it an essential tool for policy makers, researchers, and other people interested in Africa. This year's ADI addresses the issue of youth employment. The report shows that success in addressing youth employment in will not be achieved and sustained through fragmented and isolated interventions. Instead it finds that an arching guideline for addressing the youth employment challenge is the need for an integrated strategy.